Neoplasm of Inferior Rectum. Resection and Anastomosis - Palma, Eduardo C; Gutiérrez Blanco, Horacio (Cirugía del Uruguay, 1980)
A patient suffered from ulcero - vegetative Neoplasm of Inferior Rectum, 3 cms. from anal canal.